2021
DOI: 10.11604/pamj.2021.40.9.26358
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thyroid function of newly diagnosed SARS-CoV-2 infected patients in Nigeria

Abstract: Introduction the outbreak and rapid spread of the novel SARS-CoV-2, the causative agent of the coronavirus disease 2019 (COVID-19), has evolved into an unprecedented global pandemic. The infection impairs several human organs and systems, however, it is not clear how it affects thyroid function. The study therefore aimed at measuring plasma levels of thyroid hormones and Hs-CRP in COVID-19 patients and apparently healthy uninfected controls to assess the possible effect of SAR-CoV-2 infection on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Six studies recorded the thyroxine levels of healthy cohorts as control groups (n = 1052). The pooled estimates of TSH, FT3, and FT4 levels were 1.78 (95% CI, [1.56, 2.01]), 4.76 (95% CI, [4.44, 5.08]), and 14.03 (95% CI, [12.93, 15.13]), respectively ( eFigure 3 in the Supplement ) ( 14 , 18 , 36 , 40 42 ). Five studies included the thyroxine levels of non-COVID-19 pneumonia patients (n = 269) ( 14 , 18 , 42 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies recorded the thyroxine levels of healthy cohorts as control groups (n = 1052). The pooled estimates of TSH, FT3, and FT4 levels were 1.78 (95% CI, [1.56, 2.01]), 4.76 (95% CI, [4.44, 5.08]), and 14.03 (95% CI, [12.93, 15.13]), respectively ( eFigure 3 in the Supplement ) ( 14 , 18 , 36 , 40 42 ). Five studies included the thyroxine levels of non-COVID-19 pneumonia patients (n = 269) ( 14 , 18 , 42 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Nigerian population revealed that serum T3 and TSH concentrations were significantly higher in COVID 19 patients as compared to controls. 15.6% population had sick euthyroid and 6.7% had subclinical hypothyroidism 20 . A single centre retrospective study from Pakistan provided solid evidence of altered thyroid function due to pneumonia associated with Covid 19.…”
Section: Discussionmentioning
confidence: 97%
“… 6 Abnormal thyroid function was common in patients with COVID-19, particularly hyperthyroidism in another study. 7 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…6 Abnormal thyroid function was common in patients with COVID-19, particularly hyperthyroidism in another study. 7,15 The patients with hypothyroidism and subclinical hypothyroidism were more likely to be female. 16 The reasons for this gender disparity in the prevalence of thyroid disorders are not completely understood.…”
Section: Discussionmentioning
confidence: 99%